2.69. Rozwiąż równania: x ^ 2 – 4x + 4 = 0 c) 49 + 14x + x ^ 2 = 0 a) e) 10x – x ^ 2 = 25 g) – 16x = 64x ^ 2 + 1 b) 16x – 9x ^ 3 b) 9x ^ 2 – (x – 2) ^ 2 d) (x – 7) ^ 2 – (4 – 3x) ^ 2 f) 4 * (x + 3) ^ 2 – 49 * (1 – x) ^ 2 c) x ^ 3 – 4x ^ 2 + 4x f) 8y * x ^ 2 – 8yx + 2y e) 36y + 12xy + x ^ 2 * y b) x ^ 2 – 9 = 0 d) 0, 25x ^ 2 – 1 = 0 f) 25x ^ 2 – 81 = 0 h) – 0, 36x ^ 2 + 0, 49 = 0

2.69. Rozwiąż równania: x ^ 2 – 4x + 4 = 0 c) 49 + 14x + x ^ 2 = 0 a) e) 10x – x ^ 2 = 25 g) – 16x = 64x ^ 2 + 1 b) 16x – 9x ^ 3 b) 9x ^ 2 – (x – 2) ^ 2 d) (x – 7) ^ 2 – (4 – 3x) ^ 2 f) 4 * (x + 3) ^ 2 – 49 * (1 – x) ^ 2 c) x ^ 3 – 4x ^ 2 + 4x f) 8y * x ^ 2 – 8yx + 2y e) 36y + 12xy + x ^ 2 * y b) x ^ 2 – 9 = 0 d) 0, 25x ^ 2 – 1 = 0 f) 25x ^ 2 – 81 = 0 h) – 0, 36x ^ 2 + 0, 49 = 0 

Chcę dostęp do Akademii!